2021
DOI: 10.48045/001c.31528
|View full text |Cite
|
Sign up to set email alerts
|

Overview on pathogenesis and histopathological observations of hyperostosis in two fish species; Scomberoides lysan (Forsskal, 1775) and Pomacanthus sextriatus (Cuvier, 1831) collected from El- Jubail province, Saudi Arabia

Abstract: During years 2012 to 2018, two fish species, doublespotted queenfish (Scomberoides lysan) and sixbar angelfish (Pomacanthus sextriatus) were regularly examined during filleting processing in fish markets at Jubail province, Saudi Arabia. The routine fish inspection of the fillet-by products (fish skeletons) of these two species showed prominent and frequent hard circumscribed ossified masses attached to the spines. In Scomberoides lysan 60% of the examined fishes were affected and the hyperosteoid overgrowths … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…More than 28 years have elapsed since Smith‐Vaniz et al (1995) stated that hyperostosis has been reported in 22 families. Since then, 21 fish species belonging to 14 families were identified with the hyperostosis characteristics (Fjelldal et al, 2012; Jawad, 2013; Jawad et al, 2015; Jawad & Bannai, 2014; Jawad & Ibrahim, 2017; Mahmoud & Ibrahim, 2021; Matic‐Skoko & Ferri, 2009; Meunier et al, 1999; Meunier et al, 2010; Paig‐Tran et al, 2016; Smith‐Vaniz & Carpenter, 2007; Tuna et al, 2021). This anatomical anomaly has been also reported in fossilized specimens (Lidour et al, 2020; Meunier et al, 2010; Schlüter et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…More than 28 years have elapsed since Smith‐Vaniz et al (1995) stated that hyperostosis has been reported in 22 families. Since then, 21 fish species belonging to 14 families were identified with the hyperostosis characteristics (Fjelldal et al, 2012; Jawad, 2013; Jawad et al, 2015; Jawad & Bannai, 2014; Jawad & Ibrahim, 2017; Mahmoud & Ibrahim, 2021; Matic‐Skoko & Ferri, 2009; Meunier et al, 1999; Meunier et al, 2010; Paig‐Tran et al, 2016; Smith‐Vaniz & Carpenter, 2007; Tuna et al, 2021). This anatomical anomaly has been also reported in fossilized specimens (Lidour et al, 2020; Meunier et al, 2010; Schlüter et al, 1992).…”
Section: Introductionmentioning
confidence: 99%